Veteran Treatment Court Clients’ Perceptions of Procedural Justice and Recidivism - Atkin-Plunk, Cassandra A. (Criminal justice policy review, 2021)
Studies surrounding the effectiveness of veterans’ treatment courts (VTCs) are now emerging. Absent from this scholarship is an examination of the presence of procedural justice within VTCs and the influence of procedural justice on future criminal behavior of VTC clients. To begin this dialogue, this study surveys 41 clients enrolled in two VTCs in a Southern state. We explore client perceptions of procedurally just treatment by their judge and assigned supervision officer. Using an average follow-up time of 20 months, this study also examines the effects of perceptions of procedural justice on recidivism of court clients. Results find VTC clients perceive their judge and supervision officer treat them in a procedurally just manner. Interestingly, perceptions of procedural justice during interactions did not result in reduced recidivism among the current sample. Policy and program implications along with recommendations for future research are provided.